Public Interest and EU Competition Law. (June 2020) - Dunne, Niamh
While European Union (EU) competition law has long been understood as a variety of public interest law, the extent to which the rules can be applied directly to advance noneconomic public interest-oriented goals is more contentious. This contribution considers whether and how such concerns can be accommodated within the framework of Articles 101 and 102 of the Treaty on the Functioning of the European Union (TFEU). It considers both the conventional approach to addressing public interest concerns within the analytical structure of the antitrust rules and also how broader public interest objectives have shaped recent EU-level enforcement efforts in three key sectors: the liberalizing public utilities markets, the pharmaceutical sector, and the digital economy.